Safety issues of the dry storage of the spent nuclear fuel - Alyokhina, S.; Kostikov, A.; Kruhlov, S. (Вопросы атомной науки и техники, 2017)
Some issues of safety of the unique in Ukraine the Dry Spent Nuclear Fuel Storage Facility are highlighted. The analysis of temperature measurements of air, which cools storage containers of the spent nuclear fuel on the dry storage platform of the Zaporizhska NPP, is carried out. Factors, which influence on thermal conditions of storage containers, are defined. The approach for solving the problem of thermal processes identification in containers on storage platform is given. The results of investigation are shown safety of dry storage on Zaporizhska NPP. Висвітлені деякі проблеми безпеки унікального в Україні сухого сховища відпрацьованого ядерного палива. Проведено аналіз температурних замірів повітря, що охолоджує контейнери з відпрацьованим ядерним паливом на площадці сухого зберігання. Визначені фактори, що впливають на теплові режими контейнерів зберігання. Запропоновано підхід до розв’язання задачі ідентифікації теплових процесів у контейнерах на площадці сховища. Результати дослідження показали безпеку сухого зберігання палива на Запорізькій АЕС. Освещены некоторые проблемы безопасности уникального в Украине сухого хранилища отработавшего ядерного топлива. Проведен анализ температурных замеров воздуха, который охлаждает контейнеры с отработавшим ядерным топливом на площадке сухого хранения. Определены факторы, которые влияют на тепловые режимы контейнеров хранения. Предложен подход к решению задачи идентификации тепловых процессов в контейнерах на площадке хранилища. Результаты исследования показали безопасность сухого хранения топлива на Запорожской АЭС.